1985
DOI: 10.1126/science.2992093
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Binding Sites in Human Breast Carcinoma

Abstract: Gonadotropin-releasing hormone analogs can cause regression of hormone-dependent breast carcinomas. These effects are thought to be mediated through the inhibition of gonadotropic and steroid hormones. These analogs may also act directly on the tumor because they are effective in treating breast cancer in some postmenopausal women. The presence of specific binding sites for gonadotropin-releasing hormone was demonstrated in human breast carcinomas by means of a novel approach of ligand immunoblotting. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 166 publications
(87 citation statements)
references
References 22 publications
4
81
0
1
Order By: Relevance
“…The presence of GnRH receptors in breast cancer tissue [31] and the demonstration of antiproliferative actions of GnRH analogs in breast cancer cell lines [32,47,96] supported this interpretation. Antiproliferative effects of GnRH analogs and the expression of GnRH receptors have now been demonstrated in a number of cell lines of reproductive tract tumors, including prostate, uterine and ovarian cancers, and also in nonreproductive tract tumors [21,43,47,70,73,79].…”
Section: Direct Inhibition Of Proliferation and Stimulation Of Apoptomentioning
confidence: 77%
“…The presence of GnRH receptors in breast cancer tissue [31] and the demonstration of antiproliferative actions of GnRH analogs in breast cancer cell lines [32,47,96] supported this interpretation. Antiproliferative effects of GnRH analogs and the expression of GnRH receptors have now been demonstrated in a number of cell lines of reproductive tract tumors, including prostate, uterine and ovarian cancers, and also in nonreproductive tract tumors [21,43,47,70,73,79].…”
Section: Direct Inhibition Of Proliferation and Stimulation Of Apoptomentioning
confidence: 77%
“…The specific function of GnRH I and its receptor in these extrapituitary sites is unclear. However, an autocrine/paracrine function has been suggested (11,12). Linked to this hypothesis is the well-documented observation that direct application of GnRH analogs to peripheral reproductive tumor cells results in an attenuation of cellular proliferation and activation of cell death mechanisms (refs.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have suggested that this new variant may interact with the full-length GnRH receptor and impair signaling by reducing agonist-induced accumulation of inositol phosphate (17). In humans, controversial data have been obtained relating to the presence of extrapituitary GnRH-binding sites in breast (18,19), placenta (20), ovaries (21) and testis (22). Northern blot analysis failed to detect GnRHR mRNAs in any of the nonpituitary tissues examined (5).…”
Section: Introductionmentioning
confidence: 99%